Relationship between serum Sclerostin concentration and 6-minute walking distance and ABE groups in patients with Chronic obstructive pulmonary disease - Van, Thi Minh An; Vo, Tam; Phan, Thi Minh Phuong; Tran, Thi Bich Ngoc; Tran, Thi Kim Loan (Tạp chí Y Dược Huế, 2026)
Objectives: (1) Describe the clinical and paraclinical characteristics of patients with chronic obstructive pulmonary disease (COPD), (2) Investigate serum Sclerostin concentration and its relationship and correlation with 6-minute walking distance, symptom groups and ABE groups in patients with COPD. Materials and methods: Cross-sectional study on 43 patients with COPD admitted to the Department of Internal Medicine - Endocrinology - Rheumatology, Hue University of Medicine and Pharmacy Hospital, and the Department of Endocrinology - Pulmonology, Hue Central Hospital from July 2024 to June 2025. Results: The average age and BMI of the study group were 62.58 ± 8.05 years and 20.92 ± 3.01 kg/m2, respectively. Patients in the study group smoked 36.77 ± 18.83 packs/year. The proportion of patients in the GOLD I, II, III and IV groups were 2.3%, 58.1%, 27.9% and 14.0%, respectively. The average number of acute episodes was 1.24 ± 2.03 acute episodes/year. 58.1% of patients were in the multiple symptoms group and 41.9% of patients were in the few symptoms group. In addition, the proportions of patients in groups A, B and E were 25.6%, 34.9% and 39.5%, respectively. Serum sclerostin concentration in group E was statistically significantly lower than that in groups A and B (p < 0.05). The area under the ROC curve (AUC) of serum sclerostin concentration to predict stage E was 0.774 (p < 0.001). With a cut-off point ≤ 6.330 pmol/l, serum sclerostin concentration was able to predict stage E with a sensitivity of 88% and a specificity of 69% (95%CI: 1.57 – 5.24). There was a positive correlation between serum sclerostin concentration and 6-minute walk distance (r = 0.305, p < 0.05). Conclusion: Serum sclerostin concentration is a prognostic factor for disease stage and exercise capacity in patients with COPD.